Market assessment with OR applications - Anand, Adarsh; Aggrawal, Deepti; Agarwal, Mohini (Boca Raton : CRC Press, 2020)
"This Focus book offers relevant and international perspectives on OR techniques for market assessment under one canopy. It will be helpful for those who want to gain insight into understanding the managerial aspects from an analyst point of view and is a collaboration that contains plenty of OR techniques used in real-life problems faced by industries"--
OCLC-licensed vendor bibliographic record.
Keywords: Marketing; Operations research; TECHNOLOGY / Manufacturing; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Marketing / Research